Pengaruh Pengelolaan Kelas Dan Pedagogik Guru Terhadap Kualitas Belajar Pendidikan Agama Islam Kelas X Di SMA Negeri 1 Sei Rampah - Febriyanti, Indri; Ismail; Muliatno (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
The research aims to find out about "the influence of classroom management and teacher pedagogy in improving the quality of learning in class X Islamic religious education at SMA Negeri 1 Sei Rampah". Classroom management is one of the most complicated aspects of managing the learning process, but it attracts attention, both by experienced teachers and young teachers who are new to their duties. It is said to be complicated because classroom management is something that requires various criteria of skills, experience, and also the teacher's attitude and personality which has an influence on the classroom management carried out. Pedagogy is a teacher's ability to understand students, design and implement learning, develop students, and evaluate student learning outcomes to actualize the potential they have. Learning quality is the level of development of behavior in learning obtained through one's own experience. Aspects students are said to have quality of learning if you focus on the teaching and learning process (pay attention to the teacher teaching), active in class (always present and brave enough to ask questions and be able to working together with a group), and determining learning goals. The method I use is quantitative by distributing questionnaires, observation and documentation.